Tinjauan Yuridis Kawin Gantung Masyarakat Melayu Desa Dahari Indah Kecamatan Talawi Kabupaten Batu Bara - Asyrofulmuttaqin, Asyrofulmuttaqin; Nasution, Muhammad Syukri Albani (Fakultas Syariah INSURI Ponorogo, 2023)
Marriage is a sacred matter, the pillars and conditions must be fulfilled. In the Indonesian context, marriage must be registered and in an orderly administration. There are other matters that are very important for the Malay community in Batu Bara Regency, when a marriage (akad nikah) takes place, while the walimatul `urs has not been carried out, the bride and groom cannot live together, the rights and obligations of each cannot be carried out until walimatul `urs urs is held, this marriage is known as the